2018
DOI: 10.2116/analsci.18p147
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Microbial Activity and Anthraquinone-2,7-disulfonate as a Model of Humic Substances in Leaching of Iron from Hematite into Seawater

Abstract: Fertilization with a mixture of steelmaking slag and compost can affect the supply of dissolved iron used to restore seaweed beds, however, the mechanisms of iron elution from the fertilizer is not well understood. In the present study, the microorganism was isolated from Fe-fertilizer incubated in coastal seawater for 6 months and was identified as Exiguobacterium oxidotolerans T-2-2 by 16S rDNA sequencing. The iron elutability of the bacteria was proved the increasing of dissolved iron by the incubation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…30,31) This electron shuttling function is largely induced by quinone moieties. 12,16,30,31) The electron shuttling function depends on the structural features of HA. A significantly large amount of aromatic compounds was detected as fragments of the HHA by TMAH-py-GC/MS analysis, in a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30,31) This electron shuttling function is largely induced by quinone moieties. 12,16,30,31) The electron shuttling function depends on the structural features of HA. A significantly large amount of aromatic compounds was detected as fragments of the HHA by TMAH-py-GC/MS analysis, in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the microbial reduction of Fe under anaerobic conditions is a relevant mechanism that explains why soluble Fe(II) can be produced from insoluble Fe(III)-oxides. [10][11][12] The previous study observed reductive Fe elution from Fe 2 O 3 by an anaerobic bacterium, E. oxidotolerans, isolated from the fertilizer, and the reductive Fe elution was enhanced by co-existed antraquinone. 12) Quinone moieties in humic substances would also play a role as an electron acceptor/donor in the natural sediment under aquatic condition.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous study showed that bacteria isolated from Fe-fertilizer are important for iron elution at a pH range of 67. 7) We reported that Exiguobacterium oxidotolerans plays a crucial role in the dissolution of Fe(III) oxide (Fe 2 O 3 , hematite). The interaction between E. oxidotolerans and hematite was monitored, and 23 mg L ¹1 of eluted Fe species was detected after a few days of incubation.…”
Section: Introductionmentioning
confidence: 99%